POST-VACCINATED COVID-19 OXIDATIVE STRESS IN MENOPAUSE FEMALES - Deora, Vivechana; Kant, Ruchi; Kumar, Navneet (Asian Journal of Pharmaceutical and Clinical Research, 2023)
After 12 months of amenorrhea (absence of menses) and the irreversible termination of ovarian activity, menopause is identified. Menopause has a number of physiological implications, including increased abdominal obesity and a higher risk of cardiovascular and metabolic illness. Hot flashes (HF), headaches, back discomfort, stiff joints, weariness, and difficulty sleeping are all signs of menopause. Menopause begins around the age of 51. Menopause occurs prematurely in 0.3–1.1% of women. During menopause, oxidant stress (hydrogen peroxide and superoxidant anion) increases the formation of free radicals. Intermediates in enzymatic reactions that occur during cell metabolism (reactive oxygen species and reactive nitrogen) sometimes leak from enzyme molecules and interact with molecular oxygen, creating free oxygen free radicals. The molecular basis of cancer, neurodegenerative and cardiovascular diseases, diabetes, and autoimmune disorders is oxidative stress caused by free oxygen radicals. HF and irregular menses are common complaints among women, as seen in many blog entries, so there may be some research to be done. Oxidative stress causes COVID-19 post-vaccination side effects. Antioxidant supplements and menopausal hormonal treatment may lower oxidative stress and inflammation. The focus of this research is to see how oxidative stress and quality of life levels change after receiving the COVID-19 vaccination, which is used to treat HF associated with menopause.